Glass composition for glass fiber, glass fiber, glass fiber fabric, and glass fiber reinforced resin composition
A tailored glass composition with specific oxide ratios addresses non-uniformity and bubble issues in conventional glass fibers, resulting in high elasticity and low thermal expansion fibers for improved resin compositions in electronic devices.
Patent Information
- Application Number
- JP2024558300
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-07-28
- Filing Date
- 2024-07-11
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2044-07-11
AI Technical Summary
Conventional glass fiber compositions, as described in PCT/JP2023/014110, face issues with non-uniformity and the presence of bubbles due to insufficient stirring during molten glass production, leading to variations in elasticity and thermal expansion coefficients, which affect the reliability of resin compositions used in electronic devices.
A glass composition for glass fibers is formulated with specific oxide ratios, including SiO2, Al2O3, MgO, CaO, ZnO, P2O5, and MXOY (FE2O3, SnO2, CeO2, MnO2, Sb2O3, As2O3), adjusted to satisfy certain equations, to enhance elasticity and reduce thermal expansion while ensuring uniform composition and reduced bubble formation.
The solution results in glass fibers with high elasticity and low thermal expansion coefficients, achieving improved clarity and uniformity, suitable for enhancing resin compositions in electronic devices.
Smart Images

Figure 0007626968000001 
Figure 0007626968000002 
Figure 0007626968000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass composition for glass fibers, a glass fiber, a glass fiber fabric, and a glass fiber reinforced resin composition. [Background technology]
[0002] Conventionally, glass fibers have been widely used to improve the strength of resin compositions.
[0003] In recent years, with the trend toward smaller and lighter electronic devices, resin compositions for printed wiring boards and the like used in such electronic devices are required to have high rigidity and excellent dimensional stability. For this reason, glass fibers used to reinforce the resin compositions are also required to have both a high elastic modulus and a low linear expansion coefficient.
[0004] In order to achieve both a high elastic modulus and a low linear expansion coefficient for glass fibers, the present applicant has filed a patent application for a glass composition for glass fibers containing ZnO and P2O5 (Patent Application No. 2023-029848, PCT / JP2023 / 014110). Summary of the Invention [Problem to be solved by the invention]
[0005] However, the glass fibers obtained from the glass compositions for glass fibers described in Japanese Patent Application No. 2023-029848 and PCT / JP2023 / 014110 have the disadvantage that the elastic modulus and linear expansion coefficient vary.
[0006] The present inventors have thoroughly investigated the cause of the above-mentioned inconveniences and have found that, when the glass composition for glass fiber is melted to form molten glass, ZnO and P2O5 are difficult to dissolve in the early stage of melting, and therefore stirring during melting is insufficient, resulting in variation in the composition of the molten glass, and that the variation in the composition of the molten glass is remarkable in a glass composition for glass fiber containing both ZnO and P2O5, and as a result, variation occurs in the elastic modulus and linear expansion coefficient of the glass fiber obtained from the molten glass.
[0007] In addition, the variation in the composition of the molten glass in this application is a gradual composition difference occurring throughout the entire inside of the molten glass, and is different from defects such as striae and phase separation that locally cause a heterogeneous glass region or heterogeneous glass phase having a different composition from the surrounding glass. In addition, striae refers to a streaky region of several mm or less having a glass composition different from the surrounding glass composition, and phase separation refers to a phase separation phenomenon in which a single-phase molten glass forms a glass phase having a different composition of several μm or less due to heat or the like. Such heterogeneous glass regions or different glass phases have a large composition difference from the surrounding glass and a refractive index difference occurs, so they can be observed with the naked eye or optical methods, but the glass composition for glass fiber described in Patent Application No. 2023-029848 and PCT / JP2023 / 014110 does not cause defects that can be found with the naked eye, such as striae or phase separation.
[0008] That is, the variation in the molten glass composition in the present application was first discovered by the present inventors through observation by the method described below as a result of extensive research conducted by the present inventors to eliminate the above-mentioned inconvenience.
[0009] Here, as a means for stirring the molten glass during melting, it is considered to add a component that generates a gas during melting, such as Fe2O3, SnO2, CeO2, MnO2, Sb2O3, As2O3, etc., to the glass composition for glass fiber. When the component is added to the glass composition for glass fiber, the component generates a gas during melting of the molten glass, and the generated gas is expected to move upward, thereby stirring the molten glass.
[0010] On the other hand, if the components generate gas during melting of the molten glass, the clarity of the molten glass decreases and the glass filaments constituting the glass fiber contain bubbles (hollows). This can cause a problem that, when a glass fiber reinforced resin composition using the glass fiber is used to form a printed wiring board, the insulation reliability of the printed wiring board is reduced.
[0011] Therefore, an object of the present invention is to provide a glass composition for glass fiber, which can eliminate such inconveniences, obtain glass fiber having both a high elastic modulus and a low linear expansion coefficient, and can obtain molten glass having excellent composition uniformity and clarity. [Means for solving the problem]
[0012] As a result of extensive investigations to achieve this object, the inventors have discovered that, by adjusting the contents of ZnO, P2O5, and MxOy (at least one oxide selected from the group consisting of Fe2O3, SnO2, CeO2, MnO2, Sb2O3, and As2O3) in a glass composition for glass fiber having a specific composition, it is possible to obtain glass fibers that have both a high elastic modulus and a low linear expansion coefficient, and further, to make the composition of the molten glass uniform, and to reduce the amount of bubbles contained in the molten glass to increase the clarity of the molten glass, thereby arriving at the present invention.
[0013] Therefore, the glass composition for glass fiber of the present invention contains, relative to the total amount, SiO2 in the range of 42.00 to 70.00 mass%, Al2O3 in the range of 10.00 to 30.00 mass%, MgO in the range of 0.00 to 8.00 mass%, CaO in the range of 0.00 to 5.00 mass%, ZnO in the range of 2.00 to 25.00 mass%, TiO2 in the range of 0.00 to 5.00 mass%, P2O5 in the range of 2.00 to 17.30 mass%, and MxOy (at least one oxide selected from the group consisting of Fe2O3, SnO2, CeO2, MnO2, Sb2O3, and As2O3) in a total range of 0.01 to 2.00 mass%, and is characterized in that the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy the following formula (1). 0.088≦(Z / P)×M 1 / 2 ≦3.554 (1)
[0014] The glass composition for glass fiber of the present invention contains SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy in the above-mentioned ranges relative to the total amount, and thus it is possible to obtain glass fibers having a high elastic modulus and a low linear expansion coefficient.
[0015] Here, the term "glass fiber has a high elastic modulus" means that the elastic modulus of the glass fiber is 70.0 GPa or more, as measured by the following method for measuring elastic modulus, and the term "glass fiber has a low linear expansion coefficient" means that the linear expansion coefficient of the glass fiber is 3.0 ppm / K or less, as calculated by the following method for measuring linear expansion coefficient.
[0016] [Method of measuring elastic modulus] First, a glass batch adjusted to have the composition of the glass composition for glass fiber is placed in a platinum crucible with a diameter of 80 mm, heated at a temperature of 1650°C for 6 hours to melt, and then removed from the platinum crucible to obtain a homogeneous glass bulk or glass cullet. Next, the obtained glass bulk or glass cullet is annealed at a temperature of 750°C for 8 hours to obtain a test piece. Next, the test piece is processed into a test piece for measuring elastic modulus of 50mm x 50mm x 5mm using a cutting machine, for example, a diamond cutter and a polishing machine, and the elastic modulus of the test piece for measuring elastic modulus is measured by an ultrasonic pulse method according to JIS R 1602:1995.
[0017] [Method of measuring linear expansion coefficient] First, the test piece obtained in the same manner as in the case of measuring the elastic modulus is processed into a test piece for measuring linear expansion coefficient of 4 mm x 4 mm x 20 mm using a cutting machine, for example, a diamond cutter and a grinding machine. Next, the obtained test piece for measuring linear expansion coefficient is heated at a temperature increase rate of 10°C / min, and the elongation is measured at a temperature range of 50 to 200°C using a thermal expansion measuring device (manufactured by NETZSCH, product name: DIL402), and the linear expansion coefficient is calculated from the elongation.
[0018] In addition, according to the glass composition for glass fiber of the present invention, the glass composition contains SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy in the above ranges relative to the total amount, and the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy formula (1), so that when MxOy generates gas in the molten glass, the generated gas entrains the minute bubbles present in the molten glass to become large bubbles, and these large bubbles rise to the top of the molten glass and are easy to escape. As a result, the clarity of the molten glass can be increased, and bubbles (hollows) contained in the glass fiber obtained from the glass composition for glass fiber can be reduced.
[0019] Here, the molten glass having high clarity means that the number of bubbles per gram of glass bulk measured by the following clarity evaluation method is 150 or more and less than 1000.
[0020] [Method of evaluating clarity] First, a glass batch adjusted to have the composition of the glass composition for glass fiber is placed in a platinum crucible with a diameter of 80 mm, melted at a temperature of 1600°C for 3 hours, and then removed from the platinum crucible to obtain a glass bulk. Next, the obtained glass bulk is heated at a temperature of 750°C for 2 hours, and then annealed by cooling to room temperature over 8 hours to obtain a test piece. Next, the center of the obtained test piece is cut into a size of 10 mm x 15 mm using a cutting machine, such as a diamond cutter, and the surface is polished with #2000 polishing paper. Next, the number of bubbles contained in the test piece with the polished surface is measured using an optical microscope.
[0021] In addition, according to the glass composition for glass fiber of the present invention, when the large bubbles rise to the top of the molten glass, the molten glass is stirred, so that ZnO and P2O5 are easily dissolved, and the composition of the molten glass can be made uniform.
[0022] Here, the molten glass having a uniform composition means that the composition uniformity calculated by the following composition uniformity evaluation method is 10.0% or less.
[0023] [Method of evaluating composition uniformity] First, the center of a test piece obtained in the same manner as in the evaluation method of clarity is cut out using a cutting machine, such as a diamond cutter, so that the top and bottom surfaces are 10 mm x 15 mm in size, and the side surfaces are polished with #2000 abrasive paper. Next, a composition analysis is performed on the side surfaces of the test pieces with the polished surfaces by EDS (energy dispersive spectroscopy) to evaluate the composition difference between the top and bottom regions. Specifically, a field emission scanning electron microscope (FE-SEM, manufactured by JEOL Ltd., model number: JSM-IT800) and an energy dispersive spectroscopy device (manufactured by JEOL Ltd., model number: EDS30mm 2 Using a detector, an arbitrary 100μm 2In the above fields of view, area measurement is performed to measure the oxide-equivalent content (%) of each element contained in the glass composition for glass fiber. The oxide-equivalent content measurement of the elements is performed in three different areas in each of the top surface region and the bottom surface region, and the average value of the measurement results of the three areas is taken as the oxide-equivalent content of each element. For each element, the absolute value of the difference between the oxide-equivalent content in the top surface region and the oxide-equivalent content in the bottom surface region is calculated, and calculations were performed for all detected elements. The sum of the absolute values of the content differences of all elements is taken as the composition uniformity. The smaller the composition uniformity value, the smaller the variation in the composition of the molten glass (the better the uniformity).
[0024] In addition, the glass composition for glass fiber of the present invention preferably contains SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy in the above-mentioned ranges relative to the total amount, and the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy the following formula (2). 0.183≦(Z / P)×M 1 / 2 ≦1.775 (2)
[0025] The glass composition for glass fiber of the present invention contains SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy in the above-mentioned ranges relative to the total amount, and the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy formula (2), whereby a glass fiber having a high elastic modulus and a low linear expansion coefficient can be obtained, and the composition of the molten glass can be made more uniform, and the clarity of the molten glass can be further increased.
[0026] Here, "higher clarity of the molten glass" means that the number of bubbles per 1 g of glass bulk measured by the above-mentioned method for evaluating clarity is less than 150. Furthermore, "higher clarity of the molten glass" means that the composition uniformity calculated by the above-mentioned method for evaluating composition uniformity is 8.0% or less.
[0027] In addition, the glass composition for glass fiber of the present invention contains SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy in the above-mentioned ranges relative to the total amount, and the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy formula (2), and it is preferable that the glass composition further contains Fe2O3 in the range of 0.01 to 2.00 mass% and SnO2 in the range of 0.01 to 2.00 mass%, and the Fe2O3 content F and the SnO2 content S satisfy the following formula (3). 0.06≦S / F≦40.75 (3)
[0028] The glass composition for glass fiber of the present invention contains SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy in the above-mentioned ranges relative to the total amount, and when the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy formula (2), the glass composition further contains Fe2O3 in the range of 0.01 to 2.00 mass% and SnO2 in the range of 0.01 to 2.00 mass%, and the Fe2O3 content F and the SnO2 content S satisfy formula (3), glass fibers having a high elastic modulus and a low linear expansion coefficient can be obtained, the clarity of the molten glass can be further increased, and the composition of the molten glass can be made more uniform.
[0029] Here, the molten glass having a more uniform composition means that the composition uniformity calculated by the above-mentioned method for evaluating composition uniformity is 5.0% or less.
[0030] In addition, the glass composition for glass fiber of the present invention preferably contains SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy in the above-mentioned ranges relative to the total amount, and the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy the following formula (4). 0.183≦(Z / P)×M 1 / 2 ≦0.582 (4)
[0031] The glass composition for glass fiber of the present invention contains SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy in the above-mentioned ranges relative to the total amount, and the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy formula (4), whereby a glass fiber having a high elastic modulus and a low linear expansion coefficient can be obtained, and the clarity of the molten glass can be further increased, and the composition of the molten glass can be made even more uniform.
[0032] Here, the molten glass having a much more uniform composition means that the composition uniformity calculated by the above-mentioned method for evaluating composition uniformity is 3.0% or less.
[0033] The glass fiber of the present invention is characterized by containing a glass filament made of any one of the above-mentioned glass compositions for glass fiber. Also, the glass fiber fabric or glass fiber reinforced resin composition of the present invention is characterized by containing the glass fiber of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0034] Next, the embodiment of the present invention will be described in more detail.
[0035] The glass composition for glass fiber of the first aspect of this embodiment contains, based on the total amount, SiO2 in the range of 42.00 to 70.00 mass%, Al2O3 in the range of 10.00 to 30.00 mass%, MgO in the range of 0.00 to 8.00 mass%, CaO in the range of 0.00 to 5.00 mass%, ZnO in the range of 2.00 to 25.00 mass%, TiO2 in the range of 0.00 to 5.00 mass%, and 2. and a total of 0.01 to 2.00 mass% of MxOy (at least one oxide selected from the group consisting of Fe2O3, SnO2, CeO2, MnO2, Sb2O3, and As2O3), wherein the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy the following formula (1), and preferably satisfy the following formula (2). 0.088≦(Z / P)×M 1 / 2≦3.554 (1) 0.183≦(Z / P)×M 1 / 2 ≦1.775 (2)
[0036] According to the glass composition for glass fiber of the first aspect of this embodiment, by containing SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy in the above-mentioned ranges relative to the total amount, it is possible to obtain glass fibers having a high elastic modulus and a low linear expansion coefficient.
[0037] In addition, according to the glass composition for glass fiber of the first aspect of this embodiment, the glass composition contains SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy in the above ranges relative to the total amount, and the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy formula (1), so that when MxOy generates gas in the molten glass, the generated gas entrains fine bubbles present in the molten glass to form large bubbles, and these large bubbles rise to the top of the molten glass and are easy to escape. As a result, the clarity of the molten glass can be increased, and bubbles (hollows) contained in the glass fiber obtained from the glass composition for glass fiber can be reduced. In addition, the molten glass is stirred when the large bubbles rise to the top of the molten glass, so that ZnO and P2O5 are easily dissolved, and the composition of the molten glass can be made uniform.
[0038] In the molten glass, Fe2O3 generates gas mainly at a temperature range of 1400 to 1500°C, SnO2 generates gas mainly at a temperature range of 1500 to 1630°C, CeO2 generates gas at a temperature range of 1100 to 1400°C, MnO2 generates gas at a temperature range of 1100 to 1400°C, Sb2O3 generates gas at a temperature range of 1000 to 1300°C, and As2O3 generates gas at a temperature range of 1300 to 1600°C.
[0039] Furthermore, according to the glass composition for glass fiber of the first aspect of this embodiment, the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy formula (2), so that a glass fiber having a high elastic modulus and a low linear expansion coefficient can be obtained, and the composition of the molten glass can be made more uniform, and the clarity of the molten glass can be further improved.
[0040] Furthermore, the glass composition for glass fiber in the second aspect of this embodiment contains SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy in the above-mentioned ranges relative to the total amount, and when the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy formula (2), the glass composition contains Fe2O3 in the range of 0.01 to 2.00 mass% and SnO2 in the range of 0.01 to 2.00 mass%, and the Fe2O3 content F and the SnO2 content S satisfy the following formula (3). 0.06≦S / F≦40.75 (3)
[0041] According to the glass composition for glass fiber of the second aspect of this embodiment, when the glass composition contains SiO2, Al2O3, MgO, CaO, ZnO, TiO2, and MxOy in the above-mentioned ranges relative to the total amount, and the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy formula (2), the glass composition further contains Fe2O3 in the range of 0.01 to 2.00 mass% and SnO2 in the range of 0.01 to 2.00 mass%, and the Fe2O3 content F and the SnO2 content S satisfy formula (3), a glass fiber having a high elastic modulus and a low linear expansion coefficient can be obtained, the clarity of the molten glass can be further increased, and the composition of the molten glass can be further made uniform.
[0042] Furthermore, the glass composition for glass fiber of the third aspect of this embodiment contains SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy in the above-mentioned ranges relative to the total amount, and the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy the following formula (4). 0.183≦(Z / P)×M 1 / 2 ≦0.582 (4)
[0043] According to the glass composition for glass fiber of the third aspect of this embodiment, the glass composition contains SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy in the above-mentioned ranges relative to the total amount, and the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy formula (4), so that a glass fiber having a high elastic modulus and a low linear expansion coefficient can be obtained, and the clarity of the molten glass can be further increased, and the composition of the molten glass can be made even more uniform.
[0044] In the glass composition for glass fiber of each aspect of this embodiment, when the value of Z / P is large, the linear expansion coefficient of the obtained glass fiber tends to be large, and when the value of Z / P is small, the elastic modulus of the obtained glass fiber tends to be small. On the other hand, when the value of M is large, the amount of gas generated in the molten glass becomes excessive, and the clarity of the molten glass tends to be deteriorated, and when the value of M is small, the amount of gas generated in the molten glass sufficient for stirring the molten glass cannot be generated, and the uniformity of the molten glass tends to be deteriorated, and the clarity tends to be deteriorated.
[0045] So, (Z / P)×M 1 / 2 It is believed that the value of indicates the balance between the linear expansion coefficient and elastic modulus of the obtained glass fiber and the clarity and uniformity of the composition of the molten glass.
[0046] In addition, in the glass composition for glass fiber of the second aspect of this embodiment, when the value of S / F is large, the effect of stirring the molten glass in the temperature range of 1400 to 1500 ° C becomes insufficient, so the uniformity of the composition of the molten glass tends to deteriorate, and when the value of S / F is small, the effect of stirring the molten glass in the temperature range of 1500 to 1630 ° C and the effect of entraining fine bubbles become insufficient, so the uniformity and clarity of the composition of the molten glass tend to deteriorate. Therefore, it is considered that the value of S / F indicates the balance between the effect of stirring the molten glass in the temperature range of 1400 to 1500 ° C and the effect of stirring the molten glass in the temperature range of 1500 to 1630 ° C.
[0047] The value of S / F is preferably in the range of 0.20 to 14.00, and more preferably in the range of 0.30 to 1.40.
[0048] In the glass composition for glass fiber of each aspect of the present embodiment, if the content of SiO2 is less than 42.00 mass% relative to the total amount of the glass composition for glass fiber, the working temperature range is narrowed, and crystals may crystallize during spinning, causing nozzle clogging. Also, if the content of SiO2 exceeds 70.00 mass%, the 1000 poise temperature is high, melting property is deteriorated, and SiO2 that is not completely melted flows into the nozzle as a foreign matter, causing breakage during spinning, and productivity is deteriorated.
[0049] In the glass composition for glass fiber of each of the above aspects of this embodiment, the content of SiO2 relative to the total amount of the glass composition for glass fiber is preferably in the range of 44.00 to 65.00 mass%, more preferably in the range of 45.00 to 62.60 mass%, still more preferably in the range of 46.30 to 58.50 mass%, particularly preferably in the range of 47.90 to 55.90 mass%, and particularly preferably in the range of 48.90 to 54.90 mass%.
[0050] In the glass composition for glass fiber of each aspect of the present embodiment, if the content of Al2O3 is less than 10.00 mass% relative to the total amount of the glass composition for glass fiber, the 1000 poise temperature becomes high, the melting property deteriorates, and the elastic modulus decreases. Also, if the content of Al2O3 exceeds 30.00 mass%, crystals tend to precipitate, narrowing the working temperature range and worsening the spinnability.
[0051] In the glass composition for glass fiber of each of the above aspects of this embodiment, the content of Al2O3 relative to the total amount of the glass composition for glass fiber is preferably in the range of 19.50 to 28.40 mass%, more preferably in the range of 20.50 to 27.80 mass%, still more preferably in the range of 22.10 to 27.20 mass%, particularly preferably in the range of 22.60 to 26.40 mass%, and especially preferably in the range of 23.20 to 25.80 mass%.
[0052] In the glass composition for glass fiber of each of the above aspects of this embodiment, if the content of MgO exceeds 8.00 mass % relative to the total amount of the glass composition for glass fiber, glass fibers with a small linear expansion coefficient cannot be obtained.
[0053] In the glass composition for glass fiber of each of the above aspects of this embodiment, the content of MgO relative to the total amount of the glass composition for glass fiber is preferably in the range of 0.00 to 5.90 mass%, more preferably in the range of 0.50 to 5.40 mass%, even more preferably in the range of 1.10 to 4.90 mass%, particularly preferably in the range of 1.50 to 4.40 mass%, especially preferably in the range of 1.90 to 2.70 mass%, and particularly preferably in the range of 2.60 to 3.60 mass%.
[0054] In the glass composition for glass fiber of each of the above aspects of this embodiment, if the CaO content exceeds 5.00 mass % based on the total amount of the glass composition for glass fiber, the liquidus temperature becomes high and spinnability deteriorates.
[0055] In the glass composition for glass fiber of each of the above aspects of this embodiment, the content of CaO relative to the total amount of the glass composition for glass fiber is preferably in the range of 0.00 to 5.00 mass%, more preferably in the range of 0.00 to 2.50 mass%, even more preferably in the range of 0.00 to 0.90 mass%, particularly preferably in the range of 0.00 to 0.40 mass%, particularly preferably in the range of 0.00 mass% or more and less than 0.10 mass%, and particularly preferably in the range of 0.00 mass% or more and less than 0.05 mass%.
[0056] In the glass composition for glass fiber of each aspect of the present embodiment, if the content of ZnO is 2.00 mass% or less based on the total amount of the glass composition for glass fiber, the 1000 poise temperature becomes high and the melting property becomes poor. If the content of ZnO exceeds 25.00 mass%, a glass fiber having a small linear expansion coefficient cannot be obtained.
[0057] In the glass composition for glass fiber of each of the above aspects of this embodiment, the content of ZnO relative to the total amount of the glass composition for glass fiber is preferably in the range of 2.50 to 22.00 mass%, more preferably in the range of 3.0 to 18.00 mass%, even more preferably in the range of 4.10 to 14.10 mass%, particularly preferably in the range of 5.20 to 11.00 mass%, especially preferably in the range of 6.00 to 10.10 mass%, and particularly preferably in the range of 6.50 to 9.50 mass%.
[0058] In the glass composition for glass fiber of each aspect of the present embodiment, if the content of TiO2 exceeds 5.00 mass% based on the total amount of the glass composition for glass fiber, the melt viscosity cannot be reduced while maintaining a low linear expansion coefficient. In addition, the liquidus temperature becomes too high, narrowing the working temperature range.
[0059] In the glass composition for glass fiber of each of the above aspects of this embodiment, the content of TiO2 relative to the total amount of the glass composition for glass fiber is preferably in the range of 0.00 to 2.50 mass%, more preferably in the range of 0.00 to 1.80 mass%, even more preferably in the range of 0.00 to 1.20 mass%, and particularly preferably in the range of 0.00 to 0.90 mass%.
[0060] In the glass composition for glass fiber of each of the above aspects of this embodiment, if the content of P2O5 is less than 2.00 mass% relative to the total amount of the glass composition for glass fiber, the working temperature range is narrowed and crystals are likely to be crystallized during spinning, causing nozzle clogging. If the content of P2O5 exceeds 17.30 mass%, the 1000 poise temperature is high, the melting property is deteriorated, and the liquidus temperature is high, making spinning difficult.
[0061] In the glass composition for glass fiber of each of the above aspects of this embodiment, the content of P2O5 relative to the total amount of the glass composition for glass fiber is preferably in the range of 3.80 to 17.00 mass%, more preferably in the range of 5.50 to 15.50 mass%, further preferably in the range of 6.50 to 14.90 mass%, particularly preferably in the range of 8.30 to 13.50 mass%, particularly preferably in the range of 10.10 to 13.60 mass%, and particularly preferably in the range of 11.00 to 13.30 mass%.
[0062] The glass composition for glass fiber in each aspect of this embodiment contains MxOy in the range of 0.01 to 2.00 mass % based on the total amount of the glass composition for glass fiber.
[0063] MxOy is one or more oxides selected from the group consisting of Fe2O3, SnO2, CeO2, MnO2, Sb2O3, and As2O3. In order to avoid contamination of equipment due to volatilization during melting, which would prevent long-term operation, MxOy is preferably one or more oxides selected from the group consisting of Fe2O3, SnO2, CeO2, and MnO2, which are oxides of metal elements, more preferably one or more oxides selected from the group consisting of Fe2O3, SnO2, and MnO2, which are not oxides of rare earth elements, from the viewpoint of production costs, and even more preferably one or more oxides selected from the group consisting of Fe2O3 and SnO2 from the viewpoint of low toxicity of the raw material.
[0064] In the glass composition for glass fiber of each aspect of this embodiment, from the viewpoint of increasing the stirring effect of the molten glass over a long period of time until the temperature of the molten glass rises from a low temperature to a high temperature by widening the temperature range for generating gas, the glass composition for glass fiber of each aspect of this embodiment preferably contains any two or more oxides selected from the above group, and more preferably contains Fe2O3 and SnO2.
[0065] In addition, when the glass composition for glass fiber contains any two or more oxides selected from the above group as MxOy, the content M of MxOy represents the total content of all oxides contained in MxOy.
[0066] In the glass composition for glass fiber according to each aspect of the present embodiment, if the content of MxOy is less than 0.01 mass% relative to the total amount of the glass composition for glass fiber, a sufficient amount of gas cannot be generated in the molten glass to stir the molten glass. If the content of MxOy exceeds 2.00 mass%, the amount of gas generated in the molten glass becomes excessive, and the clarity of the molten glass deteriorates.
[0067] In the glass composition for glass fiber of each of the above aspects of this embodiment, the content of MxOy relative to the total amount of the glass composition for glass fiber is preferably in the range of 0.10 to 1.40 mass%, more preferably in the range of 0.15 to 1.20 mass%, further preferably in the range of 0.30 to 0.90 mass%, and particularly preferably in the range of 0.40 to 0.60 mass%.
[0068] When the glass composition for glass fiber of each of the above aspects of this embodiment contains Fe2O3, SnO2, CeO2, MnO2, Sb2O3, or As2O3, the content thereof is independently in the range of 0.01 to 2.00 mass%, preferably in the range of 0.01 to 1.50 mass%, more preferably in the range of 0.10 to 0.90 mass%, still more preferably in the range of 0.30 to 0.70 mass%, and particularly preferably in the range of 0.40 to 0.44 mass%, based on the total amount of the glass composition for glass fiber.
[0069] When the glass composition for glass fiber of each aspect of the present embodiment contains Fe2O3 and SnO2, the ratio (S / F) of the SnO2 content S to the Fe2O3 content F is preferably in the range of 0.06 to 40.75, more preferably in the range of 0.20 to 14.00, even more preferably in the range of 0.25 to 4.90, and particularly preferably in the range of 0.30 to 1.40.
[0070] In addition, the glass composition for glass fiber of the present embodiment may contain ZrO2 from the viewpoint of reducing the melt viscosity of the molten glass to facilitate fiber lengthening. When ZrO2 is contained, the content of ZrO2 relative to the total amount of the glass composition for glass fiber is, for example, in the range of 3.00 mass% or less, preferably in the range of 1.00 mass% or less, more preferably in the range of 0.60 mass% or less, even more preferably in the range of 0.40 mass% or less, particularly preferably in the range of 0.20 mass% or less, especially preferably in the range of 0.10 mass% or less, and particularly preferably in the range of 0.001 mass% or less.
[0071] The glass composition for glass fiber of the present embodiment may contain B2O3 from the viewpoint of improving spinnability and obtaining glass fibers with a small linear expansion coefficient. When B2O3 is contained, the content of B2O3 relative to the total amount of the glass composition for glass fiber is, for example, in the range of 10.00 mass% or less, preferably in the range of 7.90 mass% or less, more preferably in the range of 0.50 to 5.90 mass%, further preferably in the range of 1.00 to 4.80 mass%, and particularly preferably in the range of 1.50 to 3.50 mass%.
[0072] In addition, the glass composition for glass fiber of the present embodiment may contain F2 and Cl2. When F2 and Cl2 are contained, the total content of F2 and Cl2 relative to the total amount of the glass composition for glass fiber is, for example, in the range of 3.00 mass% or less, preferably in the range of 1.00 mass% or less, more preferably in the range of 0.40 mass% or less, even more preferably in the range of 0.20 mass% or less, particularly preferably in the range of 0.10 mass% or less, and particularly preferably in the range of 0.001 mass% or less.
[0073] The glass composition for glass fiber of the present embodiment may contain Li2O, Na2O, and K2O. When Li2O, Na2O, and K2O are contained, the total content of Li2O, Na2O, and K2O relative to the total amount of the glass composition for glass fiber is, for example, in the range of 1.00 mass% or less, preferably in the range of 0.50 mass% or less, more preferably in the range of less than 0.10 mass%, even more preferably in the range of 0.05 mass% or less, particularly preferably in the range of 0.02 mass% or less, particularly preferably in the range of 0.03 mass% or less, and most preferably in the range of 0.01 mass% or less, from the viewpoint that a large amount of Li2O, Na2O, and K2O may deteriorate the water resistance of the glass fiber and the linear expansion coefficient.
[0074] In the glass composition for glass fiber of the present embodiment, the ratio of the content of P2O5 to the content of ZnO (P2O5 / ZnO) is preferably in the range of 0.40 to 5.60. If the ratio of the content of P2O5 to the content of ZnO (P2O5 / ZnO) is less than 0.40, the working temperature range tends to be small or the linear expansion coefficient of the glass fiber made of the glass composition for glass fiber tends to be large, and if it exceeds 5.60, the 1000 poise temperature tends to be too high. The ratio of the content of P2O5 to the content of ZnO (P2O5 / ZnO) is more preferably in the range of 0.70 to 4.50, further preferably in the range of 0.80 to 3.70, particularly preferably in the range of 0.90 to 2.80, and particularly preferably in the range of 0.95 to 2.00.
[0075] In the glass composition for glass fiber of this embodiment, the total content of SiO2, Al2O3, MgO, CaO, ZnO, TiO2, P2O5, and MxOy relative to the total amount is, for example, 91.0 mass% or more, preferably 95.0 mass% or more, more preferably 98.0 mass% or more, even more preferably 99.0 mass% or more, particularly preferably 99.3 mass% or more, particularly preferably 99.5 mass% or more, especially preferably 99.7 mass% or more, and most preferably 99.9 mass% or more.
[0076] Furthermore, the glass composition for glass fiber of the present embodiment may contain oxides of Sr, Ba, Co, Ni, Cu, Cr, Mo, W, Y, La, Bi, Gd, Pr, Sc, Pb, Cd, or Yb as impurities derived from the raw materials in a total amount of less than 3.00 mass%, preferably less than 2.00 mass%, and more preferably less than 1.00 mass%, based on the total amount of the glass composition for glass fiber.
[0077] In particular, when the glass composition for glass fiber of this embodiment contains SrO, BaO, Y2O3, La2O3, Bi2O3, Gd2O3, Pr2O3, Sc2O3, or Yb2O3 as an impurity, the content thereof is preferably independently less than 0.40 mass%, more preferably less than 0.20 mass%, even more preferably less than 0.10 mass%, particularly preferably less than 0.05 mass%, particularly preferably less than 0.01 mass%, and most preferably less than 0.001 mass%, based on the total amount of the glass composition for glass fiber.
[0078] The content of each component of the glass composition for glass fiber can be measured by using an ICP emission spectrometer for the light element Li, and the content of other elements can be measured by using a wavelength dispersive X-ray fluorescence analyzer.
[0079] The measurement method can be as follows: First, a glass batch is placed in a platinum crucible and melted in an electric furnace at a temperature of 1650°C for 6 hours while stirring to obtain a homogeneous molten glass. Alternatively, glass fibers are placed in a platinum crucible and melted in an electric furnace at a temperature of 1650°C for 6 hours while stirring to obtain a homogeneous molten glass.
[0080] The glass batch is prepared by mixing glass raw materials. When organic matter is attached to the surface of the glass fiber or when the glass fiber is mainly contained as a reinforcing material in an organic matter (resin), the glass fiber is used after removing the organic matter by, for example, heating in a muffle furnace at 300 to 650°C for about 0.5 to 24 hours.
[0081] Next, the obtained molten glass is poured onto a carbon plate to produce glass cullet, and the glass cullet is then crushed and powdered to obtain glass powder.
[0082] Next, the glass powder, which is a light element, is decomposed by heating with an acid, and then quantitatively analyzed for Li using an ICP emission spectrometer. The glass powder is molded into a disk shape using a press, and the other elements are quantitatively analyzed using a wavelength-dispersive X-ray fluorescence analyzer. Specifically, the quantitative analysis using a wavelength-dispersive X-ray fluorescence analyzer can be performed by preparing a calibration curve sample based on the results measured using the fundamental parameter method, and analyzing the calibration curve method. The content of each component in the calibration curve sample can be quantitatively analyzed using an ICP emission spectrometer. The results of these quantitative analyses are converted into oxides to calculate the content and total amount of each component, and the content (mass%) of each component described above can be calculated from these values.
[0083] The glass fiber of this embodiment can be formed, for example, from the glass composition for glass fiber of each aspect of this embodiment as follows. First, based on the components contained in the ore as the glass raw material, the content of each component, and the volatilization amount of each component during the melting process, the glass raw material is mixed so as to obtain the composition of the glass composition for glass fiber of each aspect of this embodiment. Next, the mixed glass raw material (glass batch) is supplied to a melting furnace and melted at a temperature range of 1000 poise temperature or higher, specifically, at a temperature in the range of 1450 to 1650°C. Next, the glass batch (molten glass) melted at the temperature range is discharged from 100 to 8000 nozzle tips or holes of a bushing controlled at a predetermined temperature, and is cooled and solidified while being stretched by winding at a high speed to form a glass single fiber (glass filament).
[0084] When forming the glass fiber of this embodiment, the glass filament discharged from one nozzle tip or hole and cooled and solidified usually has a perfect circular cross-sectional shape and a diameter in the range of 2.0 to 35.0 μm. For applications requiring a low linear expansion coefficient, the glass filament preferably has a diameter in the range of 3.0 to 6.0 μm, more preferably a diameter in the range of 3.0 to 4.5 μm. On the other hand, when the nozzle tip has a non-circular shape and has a protrusion or a notch for quenching the molten glass, a glass filament having a non-circular (e.g., elliptical, oval) cross-sectional shape can be obtained by controlling the temperature conditions. When the glass filament has an elliptical or oval cross-sectional shape, the ratio of the major axis to the minor axis of the cross-sectional shape (major axis / minor axis) is, for example, in the range of 2.0 to 10.0, and the fiber diameter (equivalent fiber diameter) when the cross-sectional area is converted to a perfect circle is, for example, in the range of 2.0 to 35.0 μm.
[0085] The glass fiber of the present embodiment usually takes the form of a glass fiber bundle (glass strand) in which 10 to 8000 glass filaments are bundled together, and has a weight in the range of 0.3 to 10000.0 tex (g / km).
[0086] The glass fiber of the present embodiment can take various forms, such as yarn, woven fabric, knitted fabric, nonwoven fabric (including chopped strand mat and multiaxial nonwoven fabric), chopped strand, roving, powder, etc., obtained by further processing the glass strand in various ways.
[0087] According to the glass composition for glass fiber of each of the above aspects of this embodiment, the elastic modulus of the obtained glass fiber is in the range of 70.0 GPa or more, preferably in the range of 75.0 GPa or more, more preferably in the range of 78.0 GPa or more, and even more preferably in the range of 79.0 GPa or more. There is no upper limit, but it is particularly preferably in the range of 80.0 to 90.0 GPa, and particularly preferably in the range of 81.0 to 86.0 GPa.
[0088] Furthermore, according to the glass composition for glass fiber of each of the above aspects of this embodiment, the linear expansion coefficient of the obtained glass fiber is in the range of 3.0 ppm / K or less, preferably in the range of 2.9 ppm / K or less, more preferably in the range of less than 2.5 ppm / K, and although there is no particular lower limit, it is further preferably in the range of 1.5 to 2.3 ppm / K, and particularly preferably in the range of 1.8 to 2.2 ppm / K.
[0089] According to the glass composition for glass fiber of each of the above aspects of the present embodiment, the dielectric constant of the obtained glass fiber at a measurement frequency of 10 GHz is preferably in the range of 4.4 to 5.4, and the dielectric tangent of the obtained glass fiber at a measurement frequency of 10 GHz is preferably in the range of 0.0030 to 0.0060.
[0090] The glass fiber of this embodiment may be surface-coated with an organic substance for the purpose of improving the bundling of glass filaments, improving the adhesion between glass fibers and resin, improving the uniform dispersion of glass fibers in a mixture of glass fibers and resin or inorganic material, etc. Examples of such organic substances include starch, urethane resin, epoxy resin, vinyl acetate resin, acrylic resin, modified polypropylene (particularly carboxylic acid-modified polypropylene), copolymers of (poly)carboxylic acid (particularly maleic acid) and unsaturated monomers, etc.
[0091] The glass fiber of the present embodiment may be coated with a resin composition containing, in addition to these resins, a silane coupling agent, a lubricant, a surfactant, etc. The glass fiber of the present embodiment may be coated with a treatment composition that does not contain the resins and contains a silane coupling agent, a surfactant, etc.
[0092] Such a resin composition or treatment composition coats the glass fiber in a proportion ranging from 0.1 to 2.0 mass % based on the mass of the glass fiber of this embodiment in a state where it is not coated with the resin composition or treatment composition.
[0093] The glass fiber can be coated with the organic material by, for example, applying a resin solution or a resin composition solution to the glass fiber using a known method such as a roller-type applicator in the manufacturing process of the glass fiber, and then drying the glass fiber to which the resin solution or the resin composition solution has been applied. The glass fiber of this embodiment in the form of a woven fabric can be coated with the organic material by immersing the glass fiber in a treatment composition solution, and then drying the glass fiber to which the treatment composition has been applied.
[0094] Examples of the silane coupling agent include aminosilane, chlorosilane, epoxysilane, mercaptosilane, vinylsilane, acrylicsilane, and cationic silane. The silane coupling agent may be used alone or in combination of two or more of these compounds.
[0095] Examples of aminosilanes include γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-N'-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-anilinopropyltrimethoxysilane.
[0096] An example of the chlorosilane is γ-chloropropyltrimethoxysilane.
[0097] Examples of epoxy silanes include γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0098] An example of the mercaptosilane is γ-mercaptotrimethoxysilane.
[0099] Examples of vinyl silanes include vinyl trimethoxy silane and N-β-(N-vinylbenzyl aminoethyl)-γ-aminopropyl trimethoxy silane.
[0100] An example of the acrylic silane is γ-methacryloxypropyltrimethoxysilane.
[0101] Examples of cationic silanes include N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane hydrochloride, and N-phenyl-3-aminopropyltrimethoxysilane hydrochloride.
[0102] Examples of the lubricant include modified silicone oil, animal oil and its hydrogenated product, vegetable oil and its hydrogenated product, animal wax, vegetable wax, mineral wax, condensation product of higher saturated fatty acid and higher saturated alcohol, polyethyleneimine, polyalkyl polyamine alkyl amide derivative, fatty acid amide, and quaternary ammonium salt. The lubricant can be used alone or in combination of two or more kinds.
[0103] The animal oil may include beef tallow.
[0104] Examples of vegetable oils include soybean oil, coconut oil, rapeseed oil, palm oil, castor oil, and the like.
[0105] Examples of animal waxes include beeswax and lanolin.
[0106] Examples of vegetable waxes include candelilla wax and carnauba wax.
[0107] Examples of mineral waxes include paraffin wax and montan wax.
[0108] Examples of the condensation products of higher saturated fatty acids and higher saturated alcohols include stearic acid esters such as lauryl stearate.
[0109] Examples of fatty acid amides include dehydration condensates of polyethylene polyamines such as diethylenetriamine, triethylenetetramine, and tetraethylenepentamine with fatty acids such as lauric acid, myristic acid, palmitic acid, and stearic acid.
[0110] Examples of the quaternary ammonium salt include alkyltrimethylammonium salts such as lauryltrimethylammonium chloride.
[0111] The surfactant may be a nonionic surfactant, a cationic surfactant, an anionic surfactant, or an amphoteric surfactant. The surfactant may be used alone or in combination of two or more kinds.
[0112] Examples of nonionic surfactants include ethylene oxide propylene oxide alkyl ethers, polyoxyethylene alkyl ethers, polyoxyethylene-polyoxypropylene block copolymers, alkyl polyoxyethylene-polyoxypropylene block copolymer ethers, polyoxyethylene fatty acid esters, polyoxyethylene fatty acid monoesters, polyoxyethylene fatty acid diesters, polyoxyethylene sorbitan fatty acid esters, glycerol fatty acid ester ethylene oxide adducts, polyoxyethylene castor oil ethers, hydrogenated castor oil ethylene oxide adducts, alkylamine ethylene oxide adducts, fatty acid amide ethylene oxide adducts, glycerol fatty acid esters, polyglycerin fatty acid esters, pentaerythritol fatty acid esters, sorbitol fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyhydric alcohol alkyl ethers, fatty acid alkanolamides, acetylene glycol, acetylene alcohol, ethylene oxide adducts of acetylene glycol, and ethylene oxide adducts of acetylene alcohol.
[0113] Examples of cationic surfactants include alkyldimethylbenzylammonium chloride, alkyltrimethylammonium chloride, alkyldimethylethylammonium ethylsulfate, higher alkylamine acetates, higher alkylamine hydrochlorides, ethylene oxide adducts of higher alkylamines, condensates of higher fatty acids and polyalkylenepolyamines, salts of esters of higher fatty acids and alkanolamines, salts of higher fatty acid amides, imidazoline-type cationic surfactants, and alkylpyridinium salts.
[0114] Examples of anionic surfactants include higher alcohol sulfates, higher alkyl ether sulfates, α-olefin sulfates, alkylbenzene sulfonates, α-olefin sulfonates, reaction products of fatty acid halides and N-methyltaurine, dialkyl sulfosuccinates, higher alcohol phosphates, and phosphate salts of higher alcohol ethylene oxide adducts. Examples of amphoteric surfactants include amino acid amphoteric surfactants such as alkali metal alkylaminopropionates, betaine types such as alkyldimethylbetaines, and imidazoline amphoteric surfactants.
[0115] The glass fiber fabric of this embodiment contains the glass fiber of this embodiment described above. Specifically, the glass fiber fabric of this embodiment can be obtained by weaving the glass fiber of this embodiment described above as at least a part of the warp or weft by a loom known per se. Examples of the loom include a jet loom such as an air jet or water jet loom, a shuttle loom, and a rapier loom. Examples of the weaving method by the loom include a plain weave, a satin weave, a tanned weave, and a twill weave, and from the viewpoint of manufacturing efficiency, a plain weave is preferable.
[0116] In the glass fiber fabric of this embodiment, the glass fiber of this embodiment described above is preferably composed of 35 to 20,000 glass filaments having a diameter in the range of 3.0 to 21.0 μm bundled together, with a twist in the range of 0 to 1.0 turns / 25 mm, and with a mass in the range of 0.9 to 600.0 tex (g / km).
[0117] In the glass fiber fabric of this embodiment, when the above-described glass fibers of this embodiment are used as warp or weft yarns, the warp weave density is preferably in the range of 10 to 120 yarns / 25 mm, and the weft weave density is preferably in the range of 10 to 120 yarns / 25 mm.
[0118] After being woven, the glass fiber fabric of the present embodiment may be subjected to a de-oiling treatment, a surface treatment, and a fiber-opening treatment.
[0119] The deoiling treatment may be, for example, a treatment in which the glass fiber fabric is placed in a heating furnace with an atmospheric temperature in the range of 350°C to 400°C for a period in the range of 40 to 80 hours, and organic matter adhering to the glass fibers is thermally decomposed.
[0120] The surface treatment can include a treatment in which the glass fiber fabric is immersed in a solution containing the silane coupling agent or the silane coupling agent and the surfactant, excess water is squeezed out, and the fabric is then heated and dried at a temperature in the range of 80 to 180° C. for a time period in the range of 1 to 30 minutes.
[0121] Examples of the opening treatment include a treatment for expanding the yarn width of the warp yarns and the weft yarns by applying a tension in the range of 30 to 200 N to the warp yarns of the glass fiber fabric and performing opening by water flow pressure, opening by high-frequency vibration using a liquid as a medium, opening by pressure of a fluid having a surface pressure, opening by pressure using a roll, or the like.
[0122] The glass fiber fabric of this embodiment has a fiber thickness of 7.0 to 750.0 g / m 2 It is preferable that the thickness of the insulating film be in the range of 8.0 to 500.0 μm.
[0123] In the glass fiber fabric of this embodiment, the yarn width of the warp yarns is preferably in the range of 110 to 600 μm, and the yarn width of the weft yarns is preferably in the range of 110 to 600 μm.
[0124] The glass fiber fabric of the present embodiment may have a surface treatment layer containing the silane coupling agent, or the silane coupling agent and the surfactant. When the glass fiber fabric of the present embodiment includes the surface treatment layer, the surface treatment layer may have a mass of, for example, 0.03 to 1.50 mass% based on the total mass of the glass fiber fabric including the surface treatment layer.
[0125] The glass fiber reinforced resin composition of this embodiment contains the glass fiber of this embodiment described above. Specifically, the glass fiber reinforced resin composition of this embodiment contains, for example, 10 to 90 mass% of glass fiber with respect to the total amount of the glass fiber reinforced resin composition in a glass fiber reinforced resin composition containing a resin (thermoplastic resin or thermosetting resin), glass fiber, and other additives. Also, the glass fiber reinforced resin composition of this embodiment contains, for example, 90 to 10 mass% of resin with respect to the total amount of the glass fiber reinforced resin composition, and contains other additives in the range of 0 to 40 mass%.
[0126] Examples of the thermoplastic resin that forms the glass fiber reinforced resin composition of the present embodiment include polyethylene, polypropylene, polystyrene, styrene / maleic anhydride resin, styrene / maleimide resin, polyacrylonitrile, acrylonitrile / styrene (AS) resin, acrylonitrile / butadiene / styrene (ABS) resin, chlorinated polyethylene / acrylonitrile / styrene (ACS) resin, acrylonitrile / ethylene / styrene (AES) resin, acrylonitrile / styrene / methyl acrylate (ASA) resin, styrene / acrylonitrile (SAN) resin, methacrylic resin, polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), polyamide, polyacetal, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (P TT), polycarbonate, polyarylene sulfide, polyethersulfone (PES), polyphenylsulfone (PPSU), polyphenylene ether (PPE), modified polyphenylene ether (m-PPE), polyaryletherketone, liquid crystal polymer (LCP), fluororesin, polyetherimide (PEI), polyarylate (PAR), polysulfone (PSF), polyamideimide (PAI), polyaminobismaleimide (PABM), thermoplastic polyimide (TPI), polyethylene naphthalate (PEN), ethylene / vinyl acetate (EVA) resin, ionomer (IO) resin, polybutadiene, styrene / butadiene resin, polybutylene, polymethylpentene, olefin / vinyl alcohol resin, cyclic olefin resin, cellulose resin, polylactic acid, etc.
[0127] Examples of the polyethylene include high density polyethylene (HDPE), medium density polyethylene, low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and ultra-high molecular weight polyethylene.
[0128] Examples of the polypropylene include isotactic polypropylene, atactic polypropylene, syndiotactic polypropylene, and mixtures thereof.
[0129] Examples of the polystyrene include general-purpose polystyrene (GPPS), which is an atactic polystyrene having an atactic structure, high impact polystyrene (HIPS), which is GPPS with a rubber component added, and syndiotactic polystyrene having a syndiotactic structure.
[0130] Examples of the methacrylic resin include a homopolymer of one of acrylic acid, methacrylic acid, styrene, methyl acrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, and a fatty acid vinyl ester, or a copolymer of two or more of them.
[0131] Examples of the polyvinyl chloride include a vinyl chloride homopolymer polymerized by a conventionally known method such as emulsion polymerization, suspension polymerization, microsuspension polymerization, or bulk polymerization; a copolymer of a vinyl chloride monomer and a copolymerizable monomer; and a graft copolymer obtained by graft-polymerizing a vinyl chloride monomer onto a polymer.
[0132] Examples of the polyamide include polycaproamide (polyamide 6), polyhexamethylene adipamide (polyamide 66), polytetramethylene adipamide (polyamide 46), polytetramethylene sebacamide (polyamide 410), polypentamethylene adipamide (polyamide 56), polypentamethylene sebacamide (polyamide 510), polyhexamethylene sebacamide (polyamide 610), polyhexamethylene dodecamide (polyamide 612), polydecamethylene adipamide (polyamide 106), polydecamethylene adipamide (polyamide 107), polydecamethylene adipamide (polyamide 109), polydecamethylene adipamide (polyamide 110), polydecamethylene adipamide (polyamide 111), polydecamethylene adipamide (polyamide 112), polydecamethylene adipamide (polyamide 113), polydecamethylene adipamide (polyamide 114), polydecamethylene adipamide (polyamide 115), polydecamethylene adipamide (polyamide 116), polydecamethylene adipamide (polyamide 117), polydecamethylene adipamide (polyamide 118), polydecamethylene adipamide (polyamide 119), polydecamethylene adipamide (polyamide 116), polydecamethylene adipamide (polyamide 118), polydecamethylene adipamide (polyamide 119 ... Camethylene sebacamide (Polyamide 1010), Polydecamethylene dodecamide (Polyamide 1012), Polyundecane amide (Polyamide 11), Polyundecamethylene adipamide (Polyamide 116), Polydodecanamide (Polyamide 12), Polyxylene adipamide (Polyamide XD6), Polyxylene sebacamide (Polyamide XD10), Polymeta-xylylene adipamide (Polyamide MXD6), Polypara-xylylene adipamide (Polyamide PXD6), Polytetramethylene terephthalamide (Po Polyamide 4T), Polypentamethylene terephthalamide (Polyamide 5T), Polyhexamethylene terephthalamide (Polyamide 6T), Polyhexamethylene isophthalamide (Polyamide 6I), Polynonamethylene terephthalamide (Polyamide 9T), Polydecamethylene terephthalamide (Polyamide 10T), Polyundecamethylene terephthalamide (Polyamide 11T), Polydodecamethylene terephthalamide (Polyamide 12T), Polytetramethylene isophthalamide (Polyamide 4I), Poly Examples of the copolymer include one or more of the components such as bis(3-methyl-4-aminohexyl)methane terephthalamide (polyamide PACMT), polybis(3-methyl-4-aminohexyl)methane isophthalamide (polyamide PACMI), polybis(3-methyl-4-aminohexyl)methanendodecamide (polyamide PACM12), polybis(3-methyl-4-aminohexyl)methane tetradecamide (polyamide PACM14), and a copolymer of these or a mixture of these components.
[0133] Examples of the polyacetal include homopolymers having oxymethylene units as the main repeating units, and copolymers mainly composed of oxymethylene units and containing oxyalkylene units having 2 to 8 adjacent carbon atoms in the main chain.
[0134] The polyethylene terephthalate may be, for example, a polymer obtained by polycondensing terephthalic acid or a derivative thereof with ethylene glycol.
[0135] The polybutylene terephthalate may be, for example, a polymer obtained by polycondensing terephthalic acid or a derivative thereof with 1,4-butanediol.
[0136] The polytrimethylene terephthalate may be, for example, a polymer obtained by polycondensing terephthalic acid or a derivative thereof with 1,3-propanediol.
[0137] Examples of the polycarbonate include a polymer obtained by a transesterification method in which a dihydroxydiaryl compound is reacted with a carbonate ester such as diphenyl carbonate in a molten state, and a polymer obtained by a phosgene method in which a dihydroxyaryl compound is reacted with phosgene.
[0138] Examples of the polyarylene sulfide include linear polyphenylene sulfide, crosslinked polyphenylene sulfide which has been polymerized and then cured, polyphenylene sulfide sulfone, polyphenylene sulfide ether, and polyphenylene sulfide ketone.
[0139] Examples of the modified polyphenylene ether include a polymer alloy of poly(2,6-dimethyl-1,4-phenylene) ether and polystyrene, a polymer alloy of poly(2,6-dimethyl-1,4-phenylene) ether and a styrene / butadiene copolymer, a polymer alloy of poly(2,6-dimethyl-1,4-phenylene) ether and a styrene / maleic anhydride copolymer, a polymer alloy of poly(2,6-dimethyl-1,4-phenylene) ether and a polyamide, and a polymer alloy of poly(2,6-dimethyl-1,4-phenylene) ether and a styrene / butadiene / acrylonitrile copolymer.
[0140] Examples of the polyaryletherketone include polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), and polyetheretherketoneketone (PEEKK).
[0141] Examples of the liquid crystal polymer (LCP) include thermotropic liquid crystal polyesters, such as (co)polymers composed of one or more structural units selected from aromatic hydroxycarbonyl units, aromatic dihydroxy units, aromatic dicarbonyl units, aliphatic dihydroxy units, aliphatic dicarbonyl units, and the like.
[0142] Examples of the fluororesin include polytetrafluoroethylene (PTFE), perfluoroalkoxy resin (PFA), fluorinated ethylene propylene resin (FEP), fluorinated ethylene tetrafluoroethylene resin (ETFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), and ethylene / chlorotrifluoroethylene resin (ECTFE).
[0143] The ionomer (IO) resin may be a copolymer of an olefin or styrene with an unsaturated carboxylic acid, in which a portion of the carboxyl groups is neutralized with a metal ion.
[0144] Examples of the olefin / vinyl alcohol resin include an ethylene / vinyl alcohol copolymer, a propylene / vinyl alcohol copolymer, a saponified ethylene / vinyl acetate copolymer, and a saponified propylene / vinyl acetate copolymer.
[0145] Examples of the cyclic olefin resin include monocyclic compounds such as cyclohexene, polycyclic compounds such as tetracyclopentadiene, and polymers of cyclic olefin monomers.
[0146] Examples of the polylactic acid include poly-L-lactic acid, which is a homopolymer of the L-form, poly-D-lactic acid, which is a homopolymer of the D-form, and stereocomplex polylactic acid, which is a mixture thereof.
[0147] Examples of the cellulose resin include methyl cellulose, ethyl cellulose, hydroxy cellulose, hydroxy methyl cellulose, hydroxy ethyl cellulose, hydroxy ethyl methyl cellulose, hydroxy propyl methyl cellulose, cellulose acetate, cellulose propionate, cellulose butyrate, etc. Examples of the thermosetting resin forming the glass fiber reinforced resin composition of this embodiment include unsaturated polyester resin, vinyl ester resin, epoxy (EP) resin, melamine (MF) resin, phenolic resin (PF), urethane resin (PU), polyisocyanate, polyisocyanurate, polyimide (PI), urea (UF) resin, silicone (SI) resin, furan (FR) resin, benzoguanamine (BR) resin, alkyd resin, xylene resin, bismaleimide triazine (BT) resin, diallyl phthalate resin (PDAP), thermosetting polyphenylene ether resin, etc.
[0148] Specifically, the unsaturated polyester resin may be a resin obtainable by esterification reaction of an aliphatic unsaturated dicarboxylic acid with an aliphatic diol.
[0149] Examples of the vinyl ester resin include bis-based vinyl ester resins and novolac-based vinyl ester resins.
[0150] Epoxy resins include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol E type epoxy resin, bisphenol S type epoxy resin, bisphenol M type epoxy resin (4,4'-(1,3-phenylenediisopridiene) bisphenol type epoxy resin), bisphenol P type epoxy resin (4,4'-(1,4-phenylenediisopridiene) bisphenol type epoxy resin), bisphenol Z type epoxy resin (4,4'-cyclohexydiene bisphenol type epoxy resin), phenol novolac type epoxy resin, cresol novolac type epoxy resin, tetraphenol group ethane type novolac type epoxy resin, etc. Examples of epoxy resins include epoxy resins, novolac-type epoxy resins having a condensed ring aromatic hydrocarbon structure, biphenyl-type epoxy resins, aralkyl-type epoxy resins such as xylylene-type epoxy resins and phenylaralkyl-type epoxy resins, naphthylene ether-type epoxy resins, naphthol-type epoxy resins, naphthalene diol-type epoxy resins, difunctional to tetrafunctional epoxy-type naphthalene resins, binaphthyl-type epoxy resins, naphthalene aralkyl-type epoxy resins, anthracene-type epoxy resins, phenoxy-type epoxy resins, dicyclopentadiene-type epoxy resins, norbornene-type epoxy resins, adamantane-type epoxy resins, and fluorene-type epoxy resins.
[0151] The melamine resin may be a polymer obtained by polycondensation of melamine (2,4,6-triamino-1,3,5-triazine) and formaldehyde.
[0152] Examples of the phenol resin include novolac-type phenol resins such as phenol novolac resin, cresol novolac resin, and bisphenol A-type novolac resin; resole-type phenol resins such as methylol-type resole resin and dimethylene ether-type resole resin; and aryl alkylene-type phenol resins. One or a combination of two or more of these resins may be used.
[0153] Urea resins include resins obtained by condensation of urea and formaldehyde.
[0154] The thermoplastic resins or thermosetting resins may be used alone or in combination of two or more kinds.
[0155] Examples of the other additives include reinforcing fibers other than glass fibers (e.g., carbon fibers and metal fibers), fillers other than glass fibers (e.g., glass powder, talc and mica), flame retardants, ultraviolet absorbers, heat stabilizers, antioxidants, antistatic agents, flow improvers, antiblocking agents, lubricants, nucleating agents, antibacterial agents and pigments.
[0156] The glass fiber reinforced resin composition of the present embodiment can be obtained, for example, by kneading the chopped strands and the resin in a twin-screw kneader and performing injection molding using the obtained resin pellets.
[0157] The glass fiber reinforced resin composition may be obtained by a known molding method such as injection compression molding, two-color molding, hollow molding, foam molding (including supercritical fluid foam molding), insert molding, in-mold coating molding, extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, stamping molding, infusion, hand layup, spray-up, resin transfer molding, sheet molding compound method, bulk molding compound method, pultrusion method, or filament winding method.
[0158] The glass fiber reinforced resin composition of the present embodiment may be a prepreg obtained by impregnating the glass fiber fabric of the present embodiment with the resin by a method known per se and semi-curing the impregnated glass fiber fabric.
[0159] Examples of applications of the molded article made of the glass fiber reinforced resin composition of the present embodiment include electronic device housings, electronic components, vehicle exterior components, vehicle interior components, vehicle engine peripheral components, muffler-related components, high-pressure tanks, and composite materials for wind energy.
[0160] An example of the electronic component is a printed wiring board.
[0161] Examples of vehicle exterior parts include bumpers, fenders, bonnets, air dams, and wheel covers.
[0162] Examples of vehicle interior parts include door trims and ceiling materials.
[0163] Examples of vehicle engine peripheral components include an oil pan, an engine cover, an intake manifold, an exhaust manifold, and the like.
[0164] Examples of muffler-related members include sound-deadening members.
[0165] Wind energy composites include wind turbine blades and the like.
[0166] The glass fiber of the present embodiment can be suitably used as a reinforcing material for inorganic materials such as gypsum, cement, etc., other than the glass fiber reinforced resin composition of the present embodiment. For example, when used as a reinforcing material for gypsum, particularly for a gypsum board having a thickness in the range of 4 to 60 mm, the glass fiber having the glass composition in the above range can be contained in an amount of 0.1 to 4.0 mass% with respect to the total mass of the gypsum.
[0167] Next, examples of the present invention and comparative examples will be described. EXAMPLES
[0168] [Examples 1 to 12, Comparative Examples 1 to 6] For each glass batch prepared to have the composition of each glass composition for glass fiber in Examples 1 to 12 and Comparative Examples 1 to 6 shown in Tables 1 to 3, the elastic modulus, linear expansion coefficient, dielectric constant, and dielectric loss tangent were measured by the following measurement methods, and the clarity of the molten glass and the uniformity of the composition of the molten glass were evaluated by the following evaluation methods. The results are shown in Tables 1 to 3.
[0169] In addition, Comparative Example 3 has the same composition as Example 1 in PCT / JP2023 / 014110, and Comparative Example 4 has the same composition as Example 2 in Japanese Patent Application No. 2023-029848.
[0170] The elastic modulus of the glass fiber obtained from the glass composition for glass fiber in Example 1 was 82.6 GPa, the linear expansion coefficient was 2.2 ppm / K, the dielectric constant at 10 GHz was 4.7, the dielectric dissipation factor at 10 GHz was 0.0043, the dielectric constant at 28 GHz was 4.6, the dielectric dissipation factor at 28 GHz was 0.0057, the dielectric constant at 56 GHz was 4.6, and the dielectric dissipation factor at 56 GHz was 0.0071. The clarity of the molten glass obtained from the composition was "A" and the composition uniformity was 0.6%.
[0171] [Method of measuring elastic modulus] First, a glass batch adjusted to have the composition of the glass composition for glass fiber is placed in a platinum crucible with a diameter of 80 mm, heated at a temperature of 1650°C for 6 hours to melt, and then removed from the platinum crucible to obtain a homogeneous glass bulk or glass cullet. Next, the obtained glass bulk or glass cullet is annealed at a temperature of 750°C for 8 hours to obtain a test piece. Next, the test piece is processed into a test piece for measuring elastic modulus of 50mm x 50mm x 5mm using a cutting machine, for example, a diamond cutter and a polishing machine, and the elastic modulus of the test piece for measuring elastic modulus is measured by an ultrasonic pulse method according to JIS R 1602:1995.
[0172] [Method of measuring linear expansion coefficient] First, the test piece obtained in the same manner as in the case of measuring the elastic modulus is processed into a test piece for measuring linear expansion coefficient of 4 mm x 4 mm x 20 mm using a cutting machine, for example, a diamond cutter and a grinding machine. Next, the obtained test piece for measuring linear expansion coefficient is heated at a temperature increase rate of 10°C / min, and the elongation is measured at a temperature range of 50 to 200°C using a thermal expansion measuring device (manufactured by NETZSCH, product name: DIL402), and the linear expansion coefficient is calculated from the elongation.
[0173] [Method of evaluating clarity] First, a glass batch adjusted to have the composition of the glass composition for glass fiber is placed in a platinum crucible with a diameter of 80 mm, melted at a temperature of 1600 ° C for 3 hours, and then removed from the platinum crucible to obtain a glass bulk. Next, the obtained glass bulk is heated at a temperature of 750 ° C for 2 hours, and then annealed by cooling to room temperature over 8 hours to obtain a test piece. Next, the center of the obtained test piece is cut into a size of 10 mm x 15 mm using a cutting machine, such as a diamond cutter, and the surface is polished with #2000 abrasive paper. Next, the number of bubbles contained in the test piece whose surface has been polished is measured using an optical microscope, and the number of bubbles per 1 g of glass bulk is evaluated as "A" if it is less than 150 bubbles, "B" if it is 150 bubbles or more but less than 1000 bubbles, and "C" if it is 1000 bubbles or more.
[0174] [Method of evaluating composition uniformity] First, the center of a test piece obtained in the same manner as in the evaluation method of clarity is cut out using a cutting machine, such as a diamond cutter, so that the top and bottom surfaces are 10 mm x 15 mm in size, and the surface is polished with #2000 abrasive paper. Next, a composition analysis is performed on the side surface of the test piece with the polished surface by EDS (energy dispersive spectroscopy) to evaluate the composition difference between the top and bottom regions. Specifically, a field emission scanning electron microscope (FE-SEM, manufactured by JEOL Ltd., model number: JSM-IT800) and an energy dispersive spectroscopy device (manufactured by JEOL Ltd., model number: EDS30mm2 Using a detector, an arbitrary 100μm 2 In the above fields of view, area measurement is performed to measure the oxide-equivalent content (%) of each element contained in the glass composition for glass fiber. The oxide-equivalent content measurement of the elements is performed in three different areas in each of the top surface region and the bottom surface region, and the average value of the measurement results of the three areas is taken as the oxide-equivalent content of each element. For each element, the absolute value of the difference between the oxide-equivalent content in the top surface region and the oxide-equivalent content in the bottom surface region is calculated, and this is calculated for all detected elements. The sum of the absolute values of the content differences of all elements is taken as the composition uniformity. The smaller the composition uniformity value, the smaller the variation in the composition of the molten glass (the better the uniformity).
[0175] [Method of measuring dielectric constant and dielectric tangent] For the dielectric constant (dielectric constant Dk) and dielectric loss tangent (dissipation factor Df) at 10 GHz or less, first, the test piece is polished to prepare a polished test piece of 80 mm x 3 mm (1 mm thick). Next, the obtained polished test piece is dried and then stored in a room at 23°C and 60% humidity for 24 hours. Next, the dielectric constant (dielectric constant Dk) and dielectric loss tangent (dissipation factor Df) at 10 GHz are measured for the obtained polished test piece using a cavity resonator method dielectric constant measuring device ADMS01Oc1 (product name) manufactured by AET Corporation in accordance with JIS C 2565:1992.
[0176] For the dielectric constant (dielectric constant Dk) and dielectric loss tangent (dissipation factor Df) above 10 GHz, first, the test piece is polished to prepare a polished test piece of 37 mm x 37 mm (0.3 mm thick). The polished test piece obtained is then dried and stored in a room at 25°C and 50% humidity for 24 hours. The dielectric constant (dielectric constant Dk) and dielectric loss tangent (dissipation factor Df) of the polished test piece obtained at 28 GHz and 56 GHz are then measured using a balanced disk resonator method.
[0177] [Table 1]
[0178] [Table 2]
[0179] [Table 3]
[0180] From Tables 1 and 2, it is clear that the glass compositions for glass fiber of Examples 1 to 10, which contain, relative to the total amount, SiO2 in the range of 42.00 to 70.00 mass%, Al2O3 in the range of 10.00 to 30.00 mass%, MgO in the range of 0.00 to 8.00 mass%, CaO in the range of 0.00 to 5.00 mass%, ZnO in the range of 2.00 to 25.00 mass%, TiO2 in the range of 0.00 to 5.00 mass%, P2O5 in the range of 2.00 to 17.30 mass%, and MxOy in the range of 0.01 to 2.00 mass%, and in which the ZnO content Z, the P2O5 content P, and the MxOy content M satisfy the formula (1), can achieve both a high elastic modulus and a low linear expansion coefficient, can increase the clarity of the molten glass, and can make the composition of the molten glass uniform.
[0181] On the other hand, from Table 3, (Z / P)×M 1 / 2 According to the glass composition for glass fiber of Comparative Example 1, in which the value of (Z / P)×M is greater than 3.554 and falls outside the range of the formula (1), it is clear that the clarity is low and the composition of the molten glass cannot be made uniform. 1 / 2It is clear that the glass composition for glass fiber of Comparative Example 2, in which the value of is less than 0.088 and falls outside the range of the formula (1), has low clarity. It is clear that the glass compositions for glass fiber of Comparative Example 3 and Comparative Example 4, in which the MxOy content is 0.00%, have low clarity and cannot make the composition of the molten glass uniform. It is clear that the glass composition for glass fiber of Comparative Example 5, in which the ZnO content is 0.00%, cannot produce glass fiber with a high elastic modulus. It is clear that the glass composition for glass fiber of Comparative Example 6, in which the P2O5 content is 0.01%, cannot produce glass fiber with a low linear expansion coefficient.
Claims
1. A glass composition for glass fibers, comprising: SiO in the range of 42.00 to 70.00 mass% based on the total amount 2 and, Al in the range of 10.00 to 30.00 mass% 2 O 3 and, MgO in the range of 0.00 to 8.00 mass %; CaO in the range of 0.00 to 5.00 mass %; ZnO in the range of 2.00 to 25.00 mass %; TiO in the range of 0.00 to 5.00 mass% 2 and, P in the range of 2.00 to 17.30 mass% 2 O 5 and, MxOy (Fe) in the range of 0.01 to 2.00 mass% in total 2 O 3 , SnO 2 , CeO 2 , MnO 2 , Sb 2 O 3 , As 2 O 3 At least one oxide selected from the group consisting of The ZnO content Z, the P 2 O 5 and the content M of MxOy satisfy the following formula (1): 0.088≦(Z / P)×M 1/2 ≦3.554 ・・・(1)
2. The glass composition for glass fiber according to claim 1, 2 O 5 and the content M of MxOy satisfy the following formula (2): 0.183≦(Z / P)×M 1/2 ≦1.775 ・・・(2)
3. The glass composition for glass fiber according to claim 2, Fe in the range of 0.01 to 2.00 mass% 2 O 3 and, SnO in the range of 0.01 to 2.00 mass% 2 and The Fe 2 O 3 The content F of SnO 2 A glass composition for glass fiber, characterized in that the content S of the above satisfies the following formula (3). 0.06≦S / F≦40.75 ... (3)
4. The glass composition for glass fiber according to claim 1, 2 O 5 and the content M of MxOy satisfy the following formula (4): 0.183≦(Z / P)×M 1/2 ≦0.582 ・・・(4)
5. A glass fiber comprising a glass filament made of the glass composition for glass fiber according to claim 1.
6. A woven glass fiber fabric comprising the glass fiber according to claim 5.
7. A glass fiber reinforced resin composition comprising the glass fiber according to claim 5.
Citation Information
Patent Citations
Glass material with low dielectric constant and low fiberizing temperature
JP2022079402A
Glass composition for glass fiber, glass fiber, glass fiber woven fabric, and glass-fiber-reinforced resin composition
WO2022181340A1
Long glass fiber manufacturing method, and long glass fiber
WO2023127220A1
Glass composition for glass fibers, glass fiber, and glass fiber-reinforced resin molded product
WO2023276618A1
Glass composition for glass fibers, glass fiber, and glass fiber-reinforced resin molded article
WO2023276619A1